Identifying problems among seabass brackish-water cage entrepreneurs in Malaysia - Idris, Khairuddin; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'silva; Man, Norsida (Canadian Center of Science and Education, 2013)
As the strain on marine sources escalates, the aquaculture industry is becoming a viable alternative. Due to its potential to generate income for the community, interest in aquaculture is mounting. In line with this mounting interest, information with regards to the expected challenges within the industry serves as important preparation for future aquaculture entrepreneurs. Despite its importance, however, the availability of such data is lacking, and this study attempts to fill this gap by identifying the problems faced by the sea bass brackish-water cage entrepreneurs in Malaysia. The qualitative study uses in-depth interviews with aquaculture entrepreneurs who run sea bass rearing organizations at four different locations in Malaysia. Based on the analysis, four main themes are identified, namely financial, human factors, environmental and stakeholders. The ensuing discussion attempts to highlight points of interest for those who might venture into brackish-water cage aquaculture.